2020
DOI: 10.1029/2019jg005205
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude and Drivers of Methane Ebullition and Diffusion Vary on a Longitudinal Gradient in a Small Freshwater Reservoir

Abstract: Key Points CH4 ebullition rates decreased by 98% and CH4 diffusion decreased by 32% on a longitudinal gradient from reservoir inflow to dam Ebullition was driven by physical variables upstream and phytoplankton downstream; diffusion was most related to phytoplankton Despite large variation in CH4 emissions longitudinally, time series models well captured the dynamics of emissions from a small reservoir

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 103 publications
3
30
2
Order By: Relevance
“…Similarly, a clear temperature dependence of methanogenesis and/or methanotrophy may be apparent when maximal potential rates are measured (Sepulveda-Jauregui et al 2018), but less obvious in our analysis of rates measured at close to in situ conditions. Lastly, it is important to note that other studies have observed a strong relationship between temperature and sediment ebullition, a CH 4 emission pathway we do not examine here (Aben et al 2017;Davidson et al 2018;McClure et al 2020).…”
Section: Temperature and Latitudementioning
confidence: 97%
“…Similarly, a clear temperature dependence of methanogenesis and/or methanotrophy may be apparent when maximal potential rates are measured (Sepulveda-Jauregui et al 2018), but less obvious in our analysis of rates measured at close to in situ conditions. Lastly, it is important to note that other studies have observed a strong relationship between temperature and sediment ebullition, a CH 4 emission pathway we do not examine here (Aben et al 2017;Davidson et al 2018;McClure et al 2020).…”
Section: Temperature and Latitudementioning
confidence: 97%
“…The forecasting workflow used a model developed from a previous summer sampling season (2017) of CH 4 ebullition monitoring data collected at FCR to build and calibrate our forecast models (McClure et al, 2020b). In 2017, four ebullition traps were deployed and monitored weekly from 8 May to 24 October along a shallow upstream transect (McClure et al, 2020a; Figure 1). In 2019, the year of this forecasting study, we redeployed all four traps as close as possible to their original locations in 2017 and forecasted measurements collected weekly throughout the summer.…”
Section: Site Descriptionmentioning
confidence: 99%
“…There were three parameters in this model: the intercept term (β 0 ), the parameter governing the effect of the AR term (β 1 ), and the parameter governing the effect of SWI temperature (β 2 ). This model was chosen based on prior modeling work at the site, which demonstrated that ≥60% of the total reservoir-wide CH 4 ebullition was emitted from the shallow upstream transect in FCR during the ice-free period, and that there was a strong positive relationship between ebullition and sediment-water interface (SWI) temperatures (McClure et al, 2020a). We estimated the posterior distributions of the parameters in the model using a state-space Bayesian framework.…”
Section: Forecast Model and Model-fittingmentioning
confidence: 99%
See 2 more Smart Citations